PERAN NEGARA MELALUI PROGRAM KELUARGA HARAPAN DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KECEMATAN MATA OLEO KABUPATEN BOMBANA - Azhari (Journal Publicuho, 2023)
This study aims to determine the extent of the state's role through PKH in improving the welfare of the people in the Mata Oleo subdistrict, Bombana district. This study used a qualitative method using a purposive sampling technique, the data sources in this study were primary data in the form of interviews and observations and secondary data in the form of journals, books, and other materials related to this research. The role of the state through PKH in improving the welfare of the community, especially the people of the Mata Oleo district, Bombana district has been concretely actualized through 3 (three) component categories including the Education category which seeks to prosper the poor through Elementary School (SD) to High School (SMA) Education. with the hope that in the future people who receive this education can increase the welfare of their families and the environment through the knowledge they gain at school, then the state will provide increased welfare to the Mata Oleo sub-district community through social welfare assistance to people with disabilities as a form of ensuring that all Indonesian citizens are equal before the law, government and social life in general as well as the state seeks to provide protection for pregnant women as a measure to reduce the high rate of maternal mortality and to ensure the long-term survival of mothers and their children so as to improve the quality of the human growth index in the future.